2006
DOI: 10.1002/bsl.683
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of delusional disorders in the context of offending and the potential for compulsory treatment

Abstract: Delusional disorder is an uncommon mental illness with an estimated prevalence of 0.03%. Its low prevalence has likely contributed to the paucity of research interest in this area, leading to substantial gaps in knowledge concerning its treatment and management. In the absence of a robust literature, most clinicians rely on their experience and guidelines for treating schizophrenia when treating patients with delusional disorder. This article reviews the available literature that is specific to the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 91 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…In the landmark case on involuntary pharmacotherapy for restoration of competence to stand trial ( Sell v. U.S., 2003 ), the American Psychiatric Association supported the use of antipsychotic medication ( American Psychiatric Association, 2003 ), whereas the American Psychological Association rejected this approach ( American Psychological Association, 2002 ) in their respective briefs to the Supreme Court. In contrast to the pharmacotherapy of impulsive aggression, we are aware of no cross-over double-blind studies having been conducted to determine the efficacy of any agent for the treatment of this disorder ( Felthous et al, 2001 ; Smith and Buckley, 2006 ; Skelton et al, 2015 ). For whatever reason, some disorders are simply not sufficiently investigated neurobiologically and pharmacologically.…”
Section: Discussionmentioning
confidence: 99%
“…In the landmark case on involuntary pharmacotherapy for restoration of competence to stand trial ( Sell v. U.S., 2003 ), the American Psychiatric Association supported the use of antipsychotic medication ( American Psychiatric Association, 2003 ), whereas the American Psychological Association rejected this approach ( American Psychological Association, 2002 ) in their respective briefs to the Supreme Court. In contrast to the pharmacotherapy of impulsive aggression, we are aware of no cross-over double-blind studies having been conducted to determine the efficacy of any agent for the treatment of this disorder ( Felthous et al, 2001 ; Smith and Buckley, 2006 ; Skelton et al, 2015 ). For whatever reason, some disorders are simply not sufficiently investigated neurobiologically and pharmacologically.…”
Section: Discussionmentioning
confidence: 99%
“…Delusional disorder has an estimated prevalence of only 0,03% in the general population [Smith and Buckley, 2006] and the age of onset is generally in the mid-to late 30s. It mostly has an insidious onset and functioning tends to be preserved [Sadock and Sadock, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…There are no definitive treatment guidelines for DD, and it has been suggested that clinicians rely on what is known of schizophrenia management when caring for these patients. 3 Portugal et al 2 found that 81.4% of DD patients were managed with antipsychotic medication, 60% of which were on an atypical antipsychotic medication. For the somatic subtype specifically, pimozide has been classically used for treatment with one study finding 47 out of 64 patients with the somatic-type DD being treated with pimozide over a 10-year period to 2004.…”
Section: Introductionmentioning
confidence: 99%